Siracusa, EuroMediterranean Smart City - Minozzi, Luigi (TeMA - Journal of Land Use, Mobility and Environment, 2013)
About three years ago, the City of Siracusa has started a serious reflection about the crisis, about its model of development and its problems related to its territorial marginality. In this context, it lodged a service "Complex Programs and EU Policies" internal the Department of Public Works as the first embryo of the future Urban Center in Siracusa. The Smarter Cities Challenge program, sponsored by IBM, provides, for the years 2011-2012-2013 a selection through a call, a hundred cities around the world that offer a program of counseling on territorial issues, urban, social, exposed by the city in challenge. The program for 2012, selected Siracusa, the only Italian city in a hundred choices, with a theme that emphasizes the need to find methods (smart) to integrate the two systems, the industrial and the historical, cultural, into the overall Siracusa system territorial. The advent of smart policies also confirms the trend that characterized the most evolved from the most marginal realities in Europe. For the realities of the Euro-Mediterranean area, such as Siracusa, the winners model’s urban policies originate from the most evolved and developed, where the economy is more structured and able to assume the active role of actors development and urban transformations. So, a universal language of transformations really exist? The same model development produces the same results everywhere, regardless the places and the people tribe? To promote smart Siracusa means, not only, economic innovation promotion, social inclusion and environmental sustainability, but also: Siracusa intends to strengthen its image as innovation land and to evolve into a center of excellence for smart policies.